A aplicação de medidas cautelares alternativas à prisão preventiva nos crimes de tráfico de drogas - Vargas, Robson de (2013)
Housed in the area of concentration and Criminal Violence System and with the line of research the Legal and Penal Systems Contemporaries of the Graduate Program in Criminal Sciences (PPGCCrim), Pontifical Catholic University of Rio Grande do Sul (PUC / RS), this study sought to examine the application of alternative protective measures in drug trafficking crimes, in order to identify the criteria chosen by the courts for their choice and suitability keep precautionary principles, and respect for the instrumental purpose that is the object of procedural prison. Thus, it was first presented an overview of the general theory of precautionary detention, in order to determine the elements on its structure and function in criminal proceedings Brazil. So initially analyzed the concept and subject of the arrest precaution, your requirement and foundation, followed by an appreciation of the principles applicable to the subject, on the basis of precautionary imprisonment for criminal proceedings and the effects that may arise from its application. In addition, we also analyzed the species of alternative protective measures, a study that addressed the historical and dogmatic, followed by an assessment of the bail and their legal status. Finally, we presented some considerations about understanding the STF and STJ on provisional release to the crime of drug trafficking, as well as the possibility of interim measures of protection alternatives for these offenses, and was presented quantitative data obtained from analysis of Habeas Corpus judged by the Criminal Chambers of the Courts of Justice of Rio Grande do Sul, Santa Catarina and Paraná, which propose that the application of the precautionary alternatives in cases of drug trafficking constitutes an exception, especially because they are considered inadequate and inadequate in the face of violation of the guarantee of public order, and its limited application, as a rule, for those crimes in which the defendant is primary and a good record, having fixed residence, lawful work and engage small amount of drugs seized